2000
DOI: 10.1023/a:1001954604324
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Rotating Cylindrical Shells in General Relativity

Abstract: Cylindrical spacetimes with rotation are studied using the Newmann-Penrose formulas. By studying null geodesic deviations the physical meaning of each component of the Riemann tensor is given. These spacetimes are further extended to include rotating dynamic shells, and the general expression of the surface energy-momentum tensor of the shells is given in terms of the discontinuation of the first derivatives of the metric coefficients. As an application of the developed formulas, a stationary shell that genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Pereira and Wang studied the polarizations of the rotating GWs, and found that the geodesic deviation equation (9.8) is replaced by [259], D 2 η µ Dλ 2 = −R µ ναβ l ν l β η α = Φ 00 e µν o + Ψ 0 e µν + +i (Ψ 1 + Φ 01 ) e µν 03 + i (Ψ 1 + Φ 01 ) e µν 13 ] η ν , (9.19) where Ψ 1 ≡ −C µνλρ l µ n ν l λ m ρ , and 2Φ 01 ≡ (R µν − Rg µν /4) l µ m ν [259], A = e γ−ψ , e µν 03 ≡ e µ 0 e ν 3 + e µ 3 e ν 0 , e µν 13 ≡ e µ 1 e ν 3 + e µ 3 e ν 1 , 20) and e 2 , e 3 and e µν + are as defined above. It is remarkable to note that now the Ψ 0 wave has only one polarization, the "+" mode, along e 2 direction, and the "×" mode now is absent.…”
Section: B Polarizations and Faraday Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pereira and Wang studied the polarizations of the rotating GWs, and found that the geodesic deviation equation (9.8) is replaced by [259], D 2 η µ Dλ 2 = −R µ ναβ l ν l β η α = Φ 00 e µν o + Ψ 0 e µν + +i (Ψ 1 + Φ 01 ) e µν 03 + i (Ψ 1 + Φ 01 ) e µν 13 ] η ν , (9.19) where Ψ 1 ≡ −C µνλρ l µ n ν l λ m ρ , and 2Φ 01 ≡ (R µν − Rg µν /4) l µ m ν [259], A = e γ−ψ , e µν 03 ≡ e µ 0 e ν 3 + e µ 3 e ν 0 , e µν 13 ≡ e µ 1 e ν 3 + e µ 3 e ν 1 , 20) and e 2 , e 3 and e µν + are as defined above. It is remarkable to note that now the Ψ 0 wave has only one polarization, the "+" mode, along e 2 direction, and the "×" mode now is absent.…”
Section: B Polarizations and Faraday Rotationmentioning
confidence: 99%
“…A spherical ball consisting of photons cuts SO in the circle S with the point O as its center. The image of the ball at the point P is turned into a spheroid with the main major axis along a line at 45 0 with respect to e1 in the plane spanned by e1 and e3 because of the interaction of Ψ1 and Φ01, while the rays are left undeflected in the e2-direction[259].performing a rotation in the plane spanned by e µ 1 α = π/4, we have e µν 13 = e…”
mentioning
confidence: 99%
“…To study the energy conditions of the energy-momentum tensor, we consider a time-like observer with its four-velocity vector U a [26,27] U a =αu a +βv a +γw a +δz a , (4.5) whereα,β,γ andδ are arbitrary constants. The four-velocity vector U a is subjected to the condition that…”
Section: Stress-energy Tensor and Energy Conditionsmentioning
confidence: 99%
“…Here we present a series of graphs showing the components of the Einstein tensor as a function of r for five different values of b (Figs. [5][6][7][8][9]. We consider the energy momentum tensor of this thick shell in the form (35).…”
Section: Thick Cylindrical Shell Around the Line Singularity: An Apprmentioning
confidence: 99%